2014
DOI: 10.1124/dmd.114.057414
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activation of the Indoloquinazoline Alkaloids Evodiamine and Rutaecarpine by Human Liver Microsomes: Dehydrogenation and Inactivation of Cytochrome P450 3A4

Abstract: Evodiamine and rutaecarpine are the main active indoloquinazoline alkaloids of the herbal medicine Evodia rutaecarpa, which is widely used for the treatment of hypertension, abdominal pain, angina pectoris, gastrointestinal disorder, and headache. Immunosuppressive effects and acute toxicity were reported in mice treated with evodiamine and rutaecarpine. Although the mechanism remains unknown, it is proposed that metabolic activation of the indoloquinazoline alkaloids and subsequent covalent binding of reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
(43 reference statements)
1
34
1
Order By: Relevance
“…Therefore, the increased bioavailability of oral dapoxetine by evodiamine may be due to the inhibition of CYP3A4-mediated metabolism. These results are consistent with the report in that evodiamine was primarily catalyzed by heterologously expressed recombinant CYP3A4 [9]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, the increased bioavailability of oral dapoxetine by evodiamine may be due to the inhibition of CYP3A4-mediated metabolism. These results are consistent with the report in that evodiamine was primarily catalyzed by heterologously expressed recombinant CYP3A4 [9]. …”
Section: Discussionsupporting
confidence: 83%
“…In addition, the anti-tumor properties of evodiamine have drawn much attention, and growing evidences demonstrated that evodiamine showed potential anti-tumor activity through inhibiting proliferation, inducing apoptosis and reducing invasion and metastasis of various tumor cells [5,6,7]. Recently, drug metabolizing enzymes involved in the metabolism of evodiamine were investigated, including CYP3A4, CYP2C9 and CYP1A2 [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…The quinone methide intermediate reacted with thiols via Michael addition by three mechanisms, including 1,2‐, 1,4‐, or 1,6‐addition. The observed fragment m/z 607 of M3 was derived from the loss of the NAC moiety, implying the presence of benzylic thioether motif rather than phenyl thioether in this NAC adduct . Based on the MS/MS data of M3, our previous dauricine work and literatures, we proposed that the nucleophile attacked the exocyclic methylene via 1,6‐addition to form benzylic thioether conjugate.…”
Section: Discussionmentioning
confidence: 76%
“…1 The quinazoline skeleton (Chart 1) present in rutaecarpine is of huge pharmacological importance. [3][4][5][6] Even though many synthetic procedures have been reported in literature to synthesize rutaecarpine and its analogues, [4][5][6][7] studies aiming at understanding the influence of the microenvironment of such molecules on their biological activity are still a topic of interest. [3][4][5][6] Even though many synthetic procedures have been reported in literature to synthesize rutaecarpine and its analogues, [4][5][6][7] studies aiming at understanding the influence of the microenvironment of such molecules on their biological activity are still a topic of interest.…”
Section: Introductionmentioning
confidence: 99%